'Valve for Life': tackling the deficit in transcatheter treatment of heart valve disease in the UK. Issue 1 (25th March 2021) - Ali, Noman; Faour, Amir; Rawlins, John; Dawkins, Sam; Appleby, Clare E; MacCarthy, Philip; Byrne, Jonathan; Trivedi, Uday; Curzen, Nick; Banning, Adrian P; Ludman, Peter; Blackman, Daniel J
Abstract : Transcatheter aortic valve implantation (TAVI) is a proven treatment for life-threatening aortic valve disease, predominantly severe aortic stenosis. However, even among developed nations, access to TAVI is not uniform. The Valve for Life initiative was launched by the European Association of Percutaneous Cardiovascular Interventions in 2015 with the objective of improving access to transcatheter valve interventions across Europe. The UK has been identified as a country with low penetration of these procedures and has been selected as the fourth nation to be included in the initiative. Specifically, the number of TAVI procedures carried out in the UK is significantly lower than almost all other European nations. Furthermore, there is substantial geographical inequity in access to TAVI within the UK. As a consequence of this underprovision, waiting times for TAVI are long, and mortality among those waiting intervention is significant. This article reviews these issues, reports new data on access to TAVI in the UK and presents the proposals of the UK Valve for Life team to address the current problems in association with the British Cardiovascular Intervention Society.